Towards a common model for European Poetry: Challenges and solutions - Bermúdez Sabel, Helena; Díez-Platas, M.L.; Ros, Salvador; González-Blanco, Elena (My University, 2022)
This paper stems from the analysis of multiple poetic resources that were available online, as well as the results of methodological discussions with scholars of European Literature. The goal was to retrieve the informational needs of all these different sources in order to build a common data model for European Poetry (EP). Thus, by implementing a reverse engineering method, we have created the Domain Model for EP, which is an important breakthrough for making existent poetry resources interoperable. The lack of a uniform academic approach to analyse and classify poetic manifestations, the divergence of theories when comparing poetry schools from different languages and periods is some of the factors that hinder the modelling process. In this paper, we will present some of the challenges we encountered while conceptualizing the information relevant to poetic analysis and how we have worked around them. Some elements of the ontology will be presented to illustrate our modelling strategies.
Keywords: data modelling; ontology engineering